The effect of labor market regulations on training behaviour and quality : the German labor market reform as a natural experiment - Jansen, Anika [Verfasser]; Strupler Leiser, Mirjam [Verfasser]; Wenzelmann, Felix [Verfasser]; Wolter, Stefan C. [Verfasser] (My University, 2013)
"Labor market fictions are seen in many extensions of the classical human capital theory as a prerequisite for firms financing general training. The labor market reforms in Germany at the beginning of the millennium have therefore been seen by many as a danger to the firms' willingness to support the apprenticeship training system. This paper analyzes the training strategies German firms deployed to cope with the greater labor market flexibility as a result of the labor market reform. Switzerland where no reforms had taken place serves as the counterfactual. The results show that firms successfully reduced the net-costs of training by involving apprentices in more work and reducing non-productive tasks, like practicing. Contrary to the widespread fear, this adapted training strategy resulted also in a substantial increase in work-related competencies and productivity of apprentices." (Autorenreferat, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; L 6 Qualität; S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; I 2.2.1 Westeuropa; Arbeitsmarkt; Regulierung; Ausbildungsqualität; Kosten-Nutzen-Relation; Schweiz; Bundesrepublik Deutschland